A U⋅U pair-to-U.C pair mutation-induced RNA native structure destabilisation and stretching-force-induced RNA misfolding - Zhong, Zhensheng (2015)
Little is known about how a non-Watson–Crick pair affects the RNA folding dynamics. We studied the effects of a U⋅U-to-U⋅C pair mutation on the folding of a hairpin in human telomerase RNA. The ensemble thermal melting of the hairpins shows an on-pathway intermediate with the disruption of the internal loop structure containing the U⋅U/U⋅C pairs. By using optical tweezers, we applied a stretching force on the terminal ends of the hairpins to probe directly the non-nearest-neighbour effects upon the mutations. The single U⋅U to U⋅C mutations are observed to 1) lower the mechanical unfolding force by approximately 1 picoNewton (pN) per mutation without affecting the unfolding reaction transition-state position (thus suggesting that removing a single hydrogen bond affects the structural dynamics at least two base pairs away), 2) result in more frequent misfolding into a small hairpin at approximately 10 pN and 3) shift the folding reaction transition-state position towards the native hairpin structure and slightly increase the mechanical folding kinetics (thus suggesting that untrapping from the misfolded state is not the rate-limiting step).